2009
DOI: 10.1186/1743-8977-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles induce cytotoxicity in the alveolar type-II cell lines A549 and NCIH441

Abstract: Background: During the last years engineered nanoparticles (NPs) have been extensively used in different technologies and consequently many questions have arisen about the risk and the impact on human health following exposure to nanoparticles. Nevertheless, at present knowledge about the cytotoxicity induced by NPs is still largely incomplete. In this context, we have investigated the cytotoxicity induced by gold nanoparticles (AuNPs), which differed in size and purification grade (presence or absence of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 37 publications
9
114
2
3
Order By: Relevance
“…However, the use of GNP synthesised through citrate method has now been found to be harmful. Presence of reducing agent sodium citrate has caused cytotoxicity and has affected the viability and proliferation of the human alveolar type-II-like cell lines A549 and NCIH441 in vitro [38]. Therefore, the GNP synthesised in this study through green process, where plant extract was used, would be safe to use for various applications.…”
Section: Direct Relation Of Gnp Size With Polyphenols and Biochemicalmentioning
confidence: 96%
“…However, the use of GNP synthesised through citrate method has now been found to be harmful. Presence of reducing agent sodium citrate has caused cytotoxicity and has affected the viability and proliferation of the human alveolar type-II-like cell lines A549 and NCIH441 in vitro [38]. Therefore, the GNP synthesised in this study through green process, where plant extract was used, would be safe to use for various applications.…”
Section: Direct Relation Of Gnp Size With Polyphenols and Biochemicalmentioning
confidence: 96%
“…Due to their plasmonic properties, gold nanoparticles (GNPs) have been proposed as advantageous nano-sized materials for use in the various diagnostic and therapeutic applications, such as cell imaging, targeted drug delivery, thermal ablation, phototherapy [1][2][3][4][5][6][7].. To date spherical GNPs have been proven as one of the most biocompatible NP models for biological-based applications [8][9][10][11][12]. Recently, it has been reported that the specific shape of GNPs can be exploited to advantageously tune these nanomaterials for any biomedical application of choice [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium citrate covered gold particles, on the contrary, werereported to get cytotoxicity. This migh be attributed to the free citrate ions within the media [33]. Similar to a surfactant type, surface properties might play a key role in the cytotoxicity of the same particles.…”
Section: On Biodecorated Gold Nanoparticles Distributed Within Tissuementioning
confidence: 99%